2021
DOI: 10.3389/fpsyt.2021.696200
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Among Healthcare Workers During the COVID-19 Outbreak: A Study Raises Concern for Non-medical Staff in Low-Risk Areas

Abstract: Objective: To investigate the prevalence of sleep quality and post-traumatic stress disorder (PTSD) symptoms of healthcare workers (HCWs) and identify the determinants for PTSD symptoms among HCWs in high-risk and low-risk areas during the COVID-19 outbreak in China.Methods: The Pittsburgh Sleep Quality Index and the Impact of Event Scale were used to assess sleep quality and symptoms of PTSD of 421 Chinese HCWs, respectively, from January 30 to March 2, 2020. The influencing factors of PTSD symptoms were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
2
10
1
1
Order By: Relevance
“…Unsurprisingly, our research participants reported fall in job enjoyment during the COVID-19 pandemic, compared to their recall of pre-pandemic job enjoyment. This was a consistent finding for all of the staff surveyed and echo similar findings in a number of international studies (41)(42)(43). One study conducted by the British Medical Association (BMA) found that 59% of doctors described their level of exhaustion from work during the pandemic as "higher than normal" in October 2020, despite the ease of the pandemic restriction (44).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Unsurprisingly, our research participants reported fall in job enjoyment during the COVID-19 pandemic, compared to their recall of pre-pandemic job enjoyment. This was a consistent finding for all of the staff surveyed and echo similar findings in a number of international studies (41)(42)(43). One study conducted by the British Medical Association (BMA) found that 59% of doctors described their level of exhaustion from work during the pandemic as "higher than normal" in October 2020, despite the ease of the pandemic restriction (44).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, one factor which led to no significant differences in job enjoyment, satisfaction outside work, wellbeing, resilience and redeployment-related anxiety, was the staff 's type of role: e.g., patient vs. non-patient facing occupational role during the pandemic. While this seems counterintuitive as most of the previous research suggested that increased exposure to COVID-19 pandemic decreases psychological wellbeing (5,7,9,10,18,27), there have been a number of studies showing nonclinical staff to have lower wellbeing scores than HCWs (17, 31,42,58). The authors suggested that the unbalanced degrees of preparation for and support through the pandemic, could be a possible explanation for the low wellbeing scores reported by staff not directly involved in managing the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of clinically relevant trauma-related symptoms ranged from 7.4% to 35% [ 44 , 45 ]. Our study estimated the prevalence of PTSD at 7%, lower than in a previous report of 13.2% in Chinese healthcare workers [ 46 ]. A multicenter observational cohort study of 9138 healthcare workers, carried out in a convenience sample of 18 healthcare institutions from 6 Autonomous Communities in Spain, showed a 22% prevalence of PTSD [ 47 ].…”
Section: Discussioncontrasting
confidence: 76%
“…It can predict the binomial outcome of a dependent variable (target) using one or a set of independent variables (predictive) ( 16 ). Binary categorical variables are often used in empirical research in health sciences, such as History of Abortion: yes or no ( 17 ), Food Security Status: Insecure Food or Secure Food and Food Stability: <3 times or 3 times ( 18 ), Post-Traumatic Stress Disorder: yes or no ( 19 ).…”
Section: Methodsmentioning
confidence: 99%